2006
DOI: 10.1002/ab.20153
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition and moral cognition in bullying: what's wrong?

Abstract: Two different models have been proposed that describe the bully alternatively as a child lacking in social skills [Crick and Dodge, 1994], or as a cold manipulative individual, who leads gangs to achieve personal goals [Sutton et al., 1999a]. The present study examined the performance of 204 8-11-year-olds in a set of stories that assessed understanding of cognitions and emotions, in relation to their Participant Role in bullying. Moreover, children's understanding of moral emotions and proneness to moral dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
306
16
49

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(410 citation statements)
references
References 62 publications
39
306
16
49
Order By: Relevance
“…These findings are in line with previous studies, which found high levels of moral disengagement in generally aggressive youngsters and school bullies (e.g. Bandura et al, 1996;Barriga & Gibbs, 1996;Gini, 2006;Hymel et al, 2005;Menesini et al, 2003;Yadava et al, 2001). MD was also a positive predictor of c-bullying, but with smaller contribution to its explanation, compared to t-bullying.…”
Section: C-bullying/c-victimization and Individual Cognitive Mechanismssupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are in line with previous studies, which found high levels of moral disengagement in generally aggressive youngsters and school bullies (e.g. Bandura et al, 1996;Barriga & Gibbs, 1996;Gini, 2006;Hymel et al, 2005;Menesini et al, 2003;Yadava et al, 2001). MD was also a positive predictor of c-bullying, but with smaller contribution to its explanation, compared to t-bullying.…”
Section: C-bullying/c-victimization and Individual Cognitive Mechanismssupporting
confidence: 93%
“…When asked to put themselves in the role of the bully in a bullying scenario, bullies tended to report morally disengaging emotions (indifference and pride) and stressed the positive outcomes for the self by denying and distorting the consequences and by ignoring the victim. Another study (Gini, 2006) examined Italian elementary students' levels of MD and found that bullies had higher levels than victims and uninvolved students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Victims (Woods et al 2009) and those exhibiting symptoms of depression (Beck 2008;Evans et al 2005) have been shown to have numerous biases in cognitive processing, e.g., deeper encoding of negative information in memory or interpretation of ambiguous material as negative (Dearing and Gotlib 2009;Hertel and Brozovich 2010). Thus being victimized, in particular if chronic or severe, may work itself into the brain altering neuro-circuitry and social cognition (Gini 2006;Sutton et al 1999;Teicher et al 2010) and stress response (Ouellet-Morin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Bulling behavior has also been associated with increased alcohol and drug use among college students (Storch et al, 2004). Some risk factors associated with a greater likelihood of the development of bullying behavior include: having unmarried parents, having maternal authoritarian or permissive parenting, having a tendency toward moral disengagement versus moral sensibility, and being of the male gender (Gini, 2006;South & Wood, 2006;Underwood, Bernon, & Rosen, 2009). …”
Section: Bullying and School Violencementioning
confidence: 99%